2000
DOI: 10.1023/a:1009484207439
|View full text |Cite
|
Sign up to set email alerts
|

Females' Coping Styles and Control Over Poker Machine Gambling

Abstract: An investigation of the relationship between impaired control over gambling, coping strategies, and demographic variables was conducted by surveying female poker machine players (N = 163) in their gaming venues. Metropolitan (n = 14) and regional (n = 6) gaming venues in Victoria, Australia participated. Control over gambling was measured using the Impaired Control Over Gambling Scale (Baron & Dickerson, 1994). Coping strategies were measured using (Folkman et al., 1986) adaptation of the Revised Ways of Copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our results confirm that PG is related to significant psychiatric comorbidity (Crockford & el-Guebaly, 1998;Dell'Osso, Allen, & Hollander, 2005). Several studies have observed that gambling is used to regulate negative emotional estates associated to life-events, dissatisfactions, and frustrations (Burge, Pietrzak, Molina, & Petry, 2004;Grant & Kim, 2002;Hand, 1998;Jiménez-Murcia et al, 2007;Potenza et al, 2001;Scannell, Quirk, Smith, Maddern, & Dickerson, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Our results confirm that PG is related to significant psychiatric comorbidity (Crockford & el-Guebaly, 1998;Dell'Osso, Allen, & Hollander, 2005). Several studies have observed that gambling is used to regulate negative emotional estates associated to life-events, dissatisfactions, and frustrations (Burge, Pietrzak, Molina, & Petry, 2004;Grant & Kim, 2002;Hand, 1998;Jiménez-Murcia et al, 2007;Potenza et al, 2001;Scannell, Quirk, Smith, Maddern, & Dickerson, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…In relation to the processes of cognitive changes for positive emotionality, we previously discussed evidence suggesting that PGs excessively employ reappraisal and positive refocusing to upregulate positive emotions ( Navas et al., 2016 , 2017 ). Finally, response-focused strategies in relation to positive emotions have been associated with GD as wishful thinking ( Jauregui, Onaindia, & Estévez, 2017 ; Scannell, Quirk, Smith, Maddern, & Dickerson, 2000 ) and emotional expression ( Jauregui et al., 2017 ). Furthermore, interesting results came from the multidimensional investigation of impulsivity among PGs.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to stick to pre-set limits arguably reflects a loss of, or impairment in, self-control and self-regulation, which can be undermined by a variety of factors (Parke et al 2014a , b ). Such factors include an inability to regulate emotion (Scanell et al 2000 ), and the use of emotion in the decision-making process over the use of problem-focused strategy (Blaszczynski et al 1990 ).…”
Section: Limit-settingmentioning
confidence: 99%